Expenditure and financial burden for common cancers in China: a hospital-based multicentre cross-sectional study. (October 2016) - Huang, Hui-Yao; Shi, Ju-Fang; Guo, Lan-Wei; Zhu, Xin-Yu; Wang, Le; Liao, Xian-Zhen; Liu, Guo-Xiang; Bai, Ya-Na; Mao, A-Yan; Ren, Jian-Song; Sun, Xiao-Jie; Zhang, Kai; et al.
Abstract: Background: Comprehensive health economic evaluation, a key component of the Cancer Screening Program in Urban China (CanSPUC), was expected to support government policy-making on screening initiatives for common cancers (lung, breast, colorectal, oesophageal, liver, and stomach cancer) in urban China. Estimation of expenditure for cancer diagnosis and treatment from a societal perspective was an essential component. The aim of this study was to estimate direct medical and non-medical expenditure and to discern the resultant financial burden. Methods: A multicentre cross-sectional survey of patients with target cancers or precancerous lesions was conducted in 37 tertiary hospitals in 13 provinces across China, from 2012 to 2014. Each patient was interviewed with a structured questionnaire for sociodemographic, clinical, and expenditure information. Expenditure data was converted to 2014 values and presented as US. Expenditure and financial burden were quantified as a whole and by subgroups. Findings: Of the included 14 594 patients with cancer (mean age 56·7 years, 58% male), annual household income was 8607. Mean expenditure per patient was 9739 (95% CI 9612–9866), and non-medical expenditure accounted for 9·3%. Expenditure per patient with colorectal, oesophageal, lung, stomach, liver or breast cancer was 10 978 (10 636–11 321), 10 506 (10 199–10 813), 9970 (9664–10 276), 9891 (9606–10 176), 8668 (8358–8977) and 8532 (8234–8831), respectively. Expenditure increased from stage I to stage IV for colorectal, stomach, and breast cancer (p<0·0001). Out-of-pocket expenditure of newly diagnosed cancer (2 months before and 10 months after diagnosis) per cancer patient was 4947 (4875–5020), accounting for 57·5% of annual household income, presenting 77·6% of families with an unmanageable financial burden. Apart from cancer site and stage, hospital type, education, occupation, insurance type, and previous years' household income were also significant predictors of expenditure (F=247·9, 56·3, 29·7, 12·8, and 28·7, respectively; all p<0·0001) as well as self-reported financial burden (χ 2 =130·4, 495·1, 1112·2, 1009·4, and 1848·2, respectively; all p<0·0001). In addition, for the included 1532 precancerous patients, mean expenditure was 3221 (3055–3387), a third of expenditure for patients with cancer. Interpretation: Expenditure for diagnosis and treatment seemed catastrophic for patients with cancer in China, and non-medical expenditure was substantial. Expenditure and financial burden varied within subgroups, especially between patients with different degrees of lesions, suggesting that cancer screening might be cost-effective in China. Funding: National Health and Family Plan Committee of China.